STRATEGI COPING STRESS KEJADIAN BULLYING (PERUNDUNGAN) SISWA SMP DI WILAYAH KECAMATAN BANYUMANIK - Yeni Dwi Nurhidayanti; Priyadi Nugraha Prabamurti; Besar Tirto Husodo (Jurnal Kesehatan Masyarakat, 2019)
ABSTRACTThe bullying phenomenon often occurs in schools and does not receive enough attention when it can have a negative impact on victims of bullying which causes depression, stress and is also depressed so that it wants to conduct research that can lead to the need for strategies to deal with stress appropriately in accordance with the problems caused by bullying. The research was aimed to know stress coping strategies by adolscent against bullying in Junior High School (JHS) student in the Banyumanik sub-district. The study population was 89 students who were victims of bullying in their schools spread across seven Junior High School (JHS) in the Banyumanik sub-district of Semarang, the sample was 87 respondents taken using total sampling technique with the design research of descriptive analytic. Bullying data was obtained from interview technique with counseling teachers of each school. Retrieval of this research data by questionnaire. The result of the reasearch that were (52,9%) respondents who used stress coping strategies in the form of problem focused coping, while (47.1%) others used emotional focused coping strategies. In the Chi Square test, the results showed that stress coping strategies with perceived suscepbility (p-value =0,033), perceived control over outcomes (p-value = 0.049), perceived control over outcomes (p-value = 0.006).  Suggestions for victims of bullying are to remain positively related and to always get along with peers at school, for the school can do active counseling with students who are indicated trying to bullying at school. Research recommended for future research Improving future research More emphasizes strategies to deal with stress by students related to the incidence of bullying in schools in the Banyumanik District.